PENGARUH BEBERAPA JENIS PESTISIDA NABATI UNTUK MENGENDALIKAN ULAT GRAYAK Spodoptera litura F. (Lepidoptera: Noctuidae) PADA TANAMAN TEMBAKAU DELI DI LAPANGAN - Resfin Butarbutar; Maryani Cyccu Tobing; Mena Uly Tarigan (Universitas Sumatera Utara, 2013)
The influence of some botanical pesticides for handling grayak caterpillarSpodoptera litura F.(Lepidoptera: Noctuidae) on Deli tobacco. Grayak caterpillar (a kind ofcutworm) is one of an important pest in Deli Tobacco plant which can reduce production. Thepurpose of the research was to know the effectiveness of gadung storage root, babadotan, and castoroil stones with correct dosage in handling grayak caterpillar (S. litura) on Deli tobacco plants. Theresearch was conducted at Institute of Deli Tobacco PTPN II Sampali Medan, from November,2011 until January, 2012. The research used Randomized Block Design (RBD) design of non-factorwhich comprised ten treatments with three control repetitions: the solution of castor oil stones (40,80, and 120 g/l of water), the solution of babadotan (40, 80, and 120 g/l of water), and the solutionof gadung storage root (40, 80, and 120 g/l of water). The result of the research showed that thetreatment of the solution of gadung storage root with the dosage of 120g/l of water was the mosteffective with the lowest percentage of damage intencity (30.00%), the highest percentage of larvamortality (88.33%), and the highest percentage of plant production (11.22g/plot). The ineffectivetreatment was the control treatment with the highest percentage of damage intencity (49.00%), thelowest percentage of larva mortality (1.79%), and the lowest percentage of plant production(4.53g/plot).Keywords: Deli tobacco, botanical pesticides, Spodoptera litura